The Falling Price of Cement in Africa - Leone, Fabrizio; Macchiavello, Rocco; Reed, Tristan (World Bank, Washington, DC, 2021)
Prices for several intermediate inputs, including cement, are higher in developing economies—particularly in Africa. Combining data from the International Comparison Program with a global directory of cement plants we estimate an industry equilibrium model to distinguish between drivers of international price dispersion: demand, costs, conduct, and entry. Developing economies feature both higher marginal costs and higher markups. African markets are not characterized by higher barriers to entry and, if anything, feature relatively more competitive conduct. The small size of many national markets, however, limits entry and competition and explains most of the higher markups. Policy implications are discussed.